MicroRNA-101 Modulates Autophagy and Oligodendroglial Alpha-Synuclein Accumulation in Multiple System Atrophy - Valera, Elvira; Spencer, Brian; Mott, Jennifer; Trejo, Margarita; Adame, Anthony; Mante, Michael; Rockenstein, Edward; Troncoso, Juan C.; Beach, Thomas G.; Masliah, Eliezer; Desplats, Paula (Frontiers in Molecular Neuroscience, 2017)
Abstract Synucleinopathies, neurodegenerative disorders with alpha-synuclein (α-syn) accumulation, are the second leading cause of neurodegeneration in the elderly, however no effective disease-modifying alternatives exist for these diseases. Multiple system atrophy (MSA) is a fatal synucleinopathy characterized by the accumulation of toxic aggregates of α-syn within oligodendroglial cells, leading to demyelination and neurodegeneration, and the reduction of this accumulation might halt the fast progression of MSA. In this sense, the involvement of microRNAs (miRNAs) in synucleinopathies is yet poorly understood, and the potential of manipulating miRNA levels as a therapeutic tool is underexplored. In this study, we analyzed the levels of miRNAs that regulate the expression of autophagy genes in MSA cases, and investigated the mechanistic correlates of miRNA dysregulation in in vitro models of synucleinopathy. We found that microRNA-101 (miR-101) was significantly increased in the striatum of MSA patients, together with a reduction in the expression of its predicted target gene RAB5A. Overexpression of miR-101 in oligodendroglial cell cultures resulted in a significant increase in α-syn accumulation, along with autophagy deficits. Opposite results were observed upon expression of an antisense construct targeting miR-101. Stereotaxic delivery of a lentiviral construct expressing anti-miR-101 into the striatum of the MBP-α-syn transgenic mouse model of MSA resulted in reduced oligodendroglial α-syn accumulation and improved autophagy. These results suggest that miRNA dysregulation contributes to MSA pathology, with miR-101 alterations potentially mediating autophagy impairments. Therefore, therapies targeting miR-101 may represent promising approaches for MSA and related neuropathologies with autophagy dysfunction.